Isotopic (δ2H and δ13C) tracing the provenance and fate of individual fatty acids fueling migrating animals: A case study of the monarch butterfly (Danaus plexippus) - Pilecky, Matthias; Wassenaar, Leonard I.; Kainz, Martin J.; Anparasan, Libesha; Ramirez, M. Isabel; McNeil, Jeremy N.; Hobson, Keith A. (Frontiers in Ecology and Evolution, 2022)
Among long-distance migratory insects, the monarch butterfly (Danaus plexippus) is one of the most iconic, journeying up to 3,500 km fueled by nectar from flowering plants along the route. Understanding how and where monarchs obtain the needed dietary resources to fuel their long migratory flight and to concomitantly ensure energy stores for overwintering would provide new insights into the migratory strategy of this species and subsequently to focus conservation efforts. This pilot study is a first attempt to assess the biochemical composition, dynamics and the isotopic (δ2H, δ13C) composition of essential and non-essential fatty acids (FA) acquired or manufactured de novo from larval host milkweed (Ascelipias spp.) by monarch butterflies from adult emergence to overwintering. Isotope data from controlled laboratory tests suggested that adult monarchs converted their dietary energy mainly into 16:0 and 18:1 fatty acids and stored them as neutral lipids in their abdomen. The FA isotopic composition reflected dietary sources, but also subsequent isotopic fractionation from metabolism. On the other hand, δ2H values of the essential omega-3 polyunsaturated fatty acid alpha-linoleic acid (ALA) positively correlated with δ2HWing, as markers of an individual’s geographic origin thereby indicating the importance of larval diet. Additionally, in wild females, the large isotopic fractionation in δ13CALA between neutral and polar lipids suggested increased bioconversion during gravidity. Finally, δ2HLIN (linoleic acid) showed fractionation of H isotopes from larval dietary sources, indicating that catabolic processes were involved in their production. Furthermore, δ2HLIN showed a negative correlation with δ2HWing values, which could potentially be used to investigate individual life-history traits, such as migratory catabolic efforts or periods of fasting, and interpretation supported by larger variations in δ2HLIN and δ13CLIN in overwintering monarchs compared to other FA. Altogether, these results provide the first evidence that H isotopic analyses of individual fatty acids in migrating and overwintering monarchs can be used to infer the nutritional history of individuals including provenance of nectaring sites used to fuel key life history events.